Lactic Acid Production Using Lactic Acid Bacteria under Optimized Conditions - Sheeladevi, A. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Lactic acid is an organic acid widely used in the food, cosmetic, pharmaceutical and chemical industries and has received increased attention for use as a monomer for the production of biodegradable poly lactic acid. Lactic acid bacteria have the property of producing lactic acid from various fermentable carbohydrates. This process is called microbial fermentation. The genera Lactobacillus, Leuconostoc, Pediococcus and Streptococcus are important members of lactic acid bacteria. Two kinds of lactic acid bacteria are recognized as Homofermentative and Heterofermentative. The homofermentative lactic acid bacteria belong to the genera Lactobacillus casei, Streptococcus lactis, Lactobacillus delbrueckii, Lactobacillus plantarum and Pediococcus cerevisiae were used for this study. These Lactic acid bacteria were isolated from various sources such as milk, curd, whey, fermented idly dough and pickles. Effect of carbon sources, temperature, pH and inoculum levels on the growth of lactic acid bacteria were investigated. Lactobacillus delbrueckii was found to produce 135 gl-1of lactic acid from 150 gl-1 of glucose followed by Lactobacillus plantarum (120 gl-1) and Lactobacillus casei (112.5 gl-1). Maximum glucose conversion to lactic acid was observed at process conditions of pH 5.5, temperature 37oC, 10% inoculum level and fermentation period of 72 hours.